Studies on the photodynamic effects of photoactive fractions from Fagopyrum tataricum L Gaertn and Ficus auriculata Lour on skin cancer cells - Merin Rinky, K. (Department of Life Sciences, University of Calicut, 2025)
Photodynamic therapy (PDT) represents a promising alternativeto traditional cancer treatments, particularly for skin cancer, whoseincidence is increasing in India. The study investigated thephotodynamic potential of plant photosensitizers from Fagopyrumtataricum and Ficus auriculata, known for their content of fagopyrinand furan compounds, respectively. The photoactive fractions PAF1(from F. tatricum) and PAF2 (from F.auriculata) were isolated byTLC fractionation of cold ethanol extracts of the aerial parts andleaves. The presence of photosensitizers was confirmed in crudeextract by HPTLC. The efficacy of these fractions was investigated onA431 skin cancer cells using MTT assay, Trypan blue assay, caspase 3assay and cell cycle analysis. They demonstrated dose and time-dependent cytotoxicity on cancer cells upon exposure to light, whileexhibiting low toxicity compared to normal L929 cells.Thephotosensitizers present in PAF1 and PAF2 were detected usingHRLCMS and GCMS analysis. Additionally, the interactions of keycompounds with EGFR targets were supported by in silico dockingstudies. These results highlight the potential of plant-derived PDTagents for safer and more effective anticancer treatments. Furtherstudies are needed to isolate the photosensitizers from the fractions andevaluate their photodynamic toxicity through further in vitro, in vivoand clinical studies.
Keywords: Photodynamic therapy; Fagopyrum tataricum; Ficus auriculata; Fagopyrin; EGFR; Skin cancer